Intercultural Sensitivity of young bilingual Basques: some aspects to work on in the Basque educational system - Naia Eguskiza; Juan Abasolo; Aintzane Etxebarria; Aitor Iglesias (Universidad de La Rioja, 2021)
The main objective of this empirical research is to identify strengths and aspects to work on in order to attend and care for diversity in the classrooms from the point of view of intercultural awareness. To this end, after reviewing the legal framework for diversity programs, information was collected using the Intercultural Sensitivity Scale tool from 410 students (223 male and 187 female) in the Autonomous Community of the Basque Country, together with descriptive information on gender, course and mother tongue(s). The results of the analysis of the data indicate that: the mother tongue is a variable to be taken into account, since it is decisive together with the gender or the course of schooling of the students. In addition, two important points to work on in the classrooms of the Basque Autonomous Community have been identified: frustration and confidence from the point of view of gender. This shows that attention must be paid to both cultural and linguistic diversity, in the search for an inclusive education and therefore an inclusive society.